Modelos de volumen comercial, perfil de fuste y crecimiento para plantaciones clonales de Gmelina arborea Roxb. ex Sm. en Costa Rica - Quirós-Monge, Sofía (Instituto Tecnológico de Costa Rica, 2015)
Melina´s tree (Gmelina arborea) is the second species with the most reforestation area in Costa Rica, because it adaptability to different climatic conditions, fast growth and productivity. Since 90´s melina’s genetic improvement has been getting better, which has caused significant changes in stem form, taper trees, commercial height and productivity. The objectives of this thesis are, first develop a merchantable volume function for a tree stem with an age of three years clonal planting. Second, make a stem taper model and third a growth system classification for clonal planting in Costa Rica. To made the volume function was used 5 models (2 lineal models and 3 nonlineal models), and using statistical criteria was chosen the best function. To the stem taper model were used two models: Kozak and Coffré, the best model was selected trough statistical criteria and user-friendliness. The classification system of plantation growth is based on creating a method of percentiles (25%, 50% and 75%), generating three equations or functions diameter at breast high (DBH) vs age, each one of these represented an every percentile. It is recommended include and to add extra information in every model.
Proyecto de Graduación (Licenciatura en Ingeniería Forestal) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Forestal, 2015.
Keywords: Gmelina arborea; Clones; Productividad; Adaptabilidad; Silvicultura